The death, burial, and resurrection of Jesus, and the death, burial, and translation of Moses in Judaic tradition - Aus, Roger David (Studies in Judaism, 2008)
The death of Jesus, and the death of Moses in Judaic tradition -- The burial of Jesus, the burial of Moses, and the well -- The resurrection of Jesus, and the translation of Moses in Judaic tradition -- Haggadah and the questions of historicity and truth in the Gospels